Estrutura supramolecular de um derivado de perileno em filmes finos fabricados por evaporação térmica a vácuo - Fernandes, José Diego [UNESP] (2015)
The supermolecular arrangement of organic thin films is a factor that infuences both optical and electrical properties of these films and, consequently, the technology, the technological applications involving organic electronics. In this dissertation, thin films of a perylene drivative (bis butylimido perylene, acronym BuPTCD wre produced by physical vapor deposition (PVD) using vacuum thermal evaporation. The aim of this work was to investigate the supramolecular arrangement of BuPTCD films, which implies to control the thickness at nanometer scale and to determine the molecular organization, the morphology (at namo and micrometer scales) and the crystallinity, besides the stability of this arragements as a function of the temperature. Optical properties (such as absorption and emission) and electrical properties (such as conductivity and photoconductivity) were also determined. The UV-Vis absorption spectra revelead a controlled growth (uniform) of the BuPTCD films. Atomic force and optical microscopy images showed a homogeneous surface of the film at nano and micrometer scales, respectively. The X-ray diffraction showed that the BuPTCD powder and PVD film have different crystalline structures, with the BuPTCD molecules head-on oriented in the PVD films, supported on the substrate surface by the side group (FTIR). This structure favors the light emission (photoluminescence) by the formation of excimers. The thermal treatment (200ºC for 10 min) does not affect the molecular organization of the PVD films, showing a thermal stability of the BuPTCD supramolecular arrangement under these cirncumstances. The electrical measuremets (DC) showed a linear increase of the current as a function of the tension, which is characteristic of ohmic behavior. Also, th films exhibited an increase of current by 2 orders of magnitude when exposed to light (photoconductive properties). Finally, BuPTCD films were exposed to vapor of trifluorpacetic acid (TFA)...